A Severe Case of Ipilimumab-Induced Ileocolitis Refractory to Glucocorticosteroids and Infliximab - Behdod Poushanchi; Hiren Vallabh; Gorman Joel Reynolds (Case Reports in Gastrointestinal Medicine)
Ipilimumab is a monoclonal antibody that works as an immunotherapeutic agent through selective targeting of T cells to strengthen the response to metastatic melanoma. It is well known that this pharmaceutical agent can cause the adverse effect of colitis. We report a rare presentation of ileocolitis refractory to both glucocorticosteroids and infliximab with a resultant pneumatosis and perforation requiring subtotal colectomy and end ileostomy.